The Solid Waste Management of Kaeng Sian Subdistrict Administrative Organization, Mueang District, Kanchanaburi Province - Samathi, Apiwat; Likhitthammarot, Pornchai; Khaisang, Nisit; Chinpa , Thitiphong (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2025)
The purpose of this research was to: 1) examine the condition of the area, the issues, and the causes of the residual waste problem at the Kaeng Sian Subdistrict Administrative Organization’s waste disposal site, and 2) investigate the management approaches for addressing residual waste at the site in Mueang District, Kanchanaburi Province. This study employed a mixed-methods approach, using interviews to collect data from 53 individuals including administrators, local leaders, government officials involved in waste management, and residents affected by waste-related issues. Additionally, questionnaires were used to gather data from a sample of 363 local residents. Qualitative data were analyzed using descriptive analysis while quantitative data were analyzed using percentage calculations. The study findings revealed that: 1. The area was in poor shape with a lot of rubbish that hadn’t been buried. The issue of residual waste encompassed both the issue of waste leachate seeping into agricultural areas and the issue of a significant volume of residual waste. The causes of the problem included the increasing amount of solid waste, the lack of proper landfill management following sanitary regulations, delays in procurement and waste management operations under the Government Procurement and Inventory Management Act B.E. 2560, and ineffective collaboration among the government, private sector, and public sector in addressing the problem. 2. The waste management approach focused on enhancing spatial management efficiency while preventing and reducing pollution at the source (waste disposal site). This was accomplished through a structured intervention plan comprising urgent (short-term), medium-term, and long-term measures.